A first principle study of adsorption of two proximate nitrogen atoms on graphene. Issue 23 (25th July 2014) - Rani, Babita; Dharamvir, Keya
<x xml:space="preserve">Abstract</x> Different possible configurations of two nitrogen‐adatoms on graphene are studied using density functional theory. Adsorption of single nitrogen atom on the bridge site of graphene is accompanied by distortion of the sheet. Electronically, this case amounts to p‐type doping. Two N atoms adsorbed on the graphene sheet can share a bond in two ways. They acquire positions either just above two adjacent carbon atoms or they form a bridge across opposite bonds of a hexagon in the sheet. Both these configurations also induce structural distortion of the sheet. Another stable configuration consists of two N atoms bonded as an N2 molecule physisorbed on the graphene sheet. It is also possible to adsorb two N atoms on opposite sides of the graphene sheet, bonded to the same two C atoms. Moreover, two N atoms can be individually adsorbed on alternate bridge sites of neighboring hexagons experiencing a repulsion, the energy for which arises from the additional distortion of the graphene sheet. The densities of states near the Fermi level are found to be dependent on the adsorption configurations of two nitrogen atoms on graphene. Thus the electronic properties of graphene can be controlled by the selective adsorption of two nitrogen atoms. © 2014 Wiley Periodicals, Inc.